Technical review of culvert design at overseas and in Malaysia/ Mohamad Azhari Ghazali - Ghazali, Mohamad Azhari (1991)
Highway drainage structure have been found to constitute about one fourth of highway construction costs. Hence it is worth while paying much attention to them since proper design and construction of these structures could save much money. Highways cross many natural drainage channels and the water carried by these channels must be conveyed across the right of way witout obstructing the flow in the channel upstream of the road and causing damage to property outside of the right of way. Notable of these structures and one of the most frequently used is the CULVETRT. A culvert is defined as an artificial water passage under road, a railroad or canal. It applies not only to a drainage opening beneath an embankment as used in highway and railway work, but to any short, closed conduit.